Estudo de solventes alternativos para extração de aromáticos - Mesquita, Francisca Maria Rodrigues (2015)
Aromatic hydrocarbons are chemical compounds of great interest in the petrochemical industry. These are commonly derived from reformed naphtha, which are in multicomponent mixtures with aliphatic hydrocarbons. The separation of these components is realized, generally, the liquid-liquid extraction process. In this process, the sulfolane is the most widely used solvent. However, this has some disadvantages such as high cost. For this reason, many studies are developed by the academic community in order to propose alternative solvents to replace the exclusive use of sulfolane by compounds that are important features like good selectivity, easy recoverability and low costs. Given the above, this study main aims to determine liquid-liquid equilibrium data (LLE) to study the ability of solvents [diethylene glycol (DEG), triethylene glycol (TEG), glycerol and 2-hydroxyethyl amine format (2-HEAF)] in extracting aromatic mixtures with aliphatic. The physical properties also of great importance in the understanding of the behavior and interactions that occur in liquid mixtures. Thus, in this study were also studied the density and viscosity of solvent extractors aromatic. The experimental methodology for the determination of LLE data was initially validated by reproducing the literature, and the results showed good agreement between these data. After the method has been validated, solubility curves and tie-lines were constructed for systems containing decane + toluene + DEG (+ TEG, + glycerol, + 2-HEAF, + sulfolane) at T = (303.15 and 333.15) K. The composition data of tie-lines, obtained experimentally, were used to calculate the selectivity parameter and the distribution coefficient. With this data, it can be concluded that all the solvents studied have a good capacity for toluene extraction from mixtures with decane. However, the glycerol has presented as the most promising solvent for aromatics extraction. Finally, the experimental data were correlated through the thermodynamic activity coefficient models, NRTL and UNIQUAC. The results were considered satisfactory, noting that the NRTL was the model that presented minor deviations in compositions. Thus, best represented the LLE data for the systems studied